2010
DOI: 10.1021/es9034733
|View full text |Cite
|
Sign up to set email alerts
|

A Time Trend Study of Significantly Elevated Perfluorocarboxylate Levels in Humans after Using Fluorinated Ski Wax

Abstract: A time trend study focusing on ski waxing technicians' exposure to perfluorinated chemicals (PFCs) from fluorinated wax fumes was performed in 2007/2008. Levels of eight perfluorocarboxylates and three perfluorosulfonates were analyzed in monthly blood samples from eight technicians. Samples were collected before the ski season, i.e., preseason, then at four FIS World Cup competitions in cross country skiing, and finally during an unexposed 5-month postseason period. The perfluorinated carboxylates perfluorohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 40 publications
7
116
1
1
Order By: Relevance
“…The half-life range for PFOA was later confirmed in studies of general populations from Germany and the US exposed to PFOA through contaminated drinking water (Bartell et al 2009;Hölzer et al 2009;Seals et al 2010). Two recent studies on exposures of professional ski waxing technicians indicated long elimination half-lives for PFNA, PFDA and PFUnDA as well (Freberg et al 2010;Nilsson et al 2010). In contrast the half-life of PFBS in six occupationally exposed workers was found to be around one month (Olsen et al 2009a).…”
Section: Physical-chemical Properties and Pharmacokineticsmentioning
confidence: 90%
See 1 more Smart Citation
“…The half-life range for PFOA was later confirmed in studies of general populations from Germany and the US exposed to PFOA through contaminated drinking water (Bartell et al 2009;Hölzer et al 2009;Seals et al 2010). Two recent studies on exposures of professional ski waxing technicians indicated long elimination half-lives for PFNA, PFDA and PFUnDA as well (Freberg et al 2010;Nilsson et al 2010). In contrast the half-life of PFBS in six occupationally exposed workers was found to be around one month (Olsen et al 2009a).…”
Section: Physical-chemical Properties and Pharmacokineticsmentioning
confidence: 90%
“…Increased PFOA concentrations have also been observed in a population living close to a manufacturing site (Emmett et al 2006). Further, two Nordic studies have seen elevated concentrations of PFCAs in serum from professional skiwaxers (Freberg et al 2010;Nilsson et al 2010). No clear regional differences have been observed for general populations.…”
Section: Human Biomonitoring (Internal Dose)mentioning
confidence: 97%
“…Several studies confirm that PFAS concentrations in human serum are significantly higher when workers were occupationally exposed. 71,81,82 However, those studies mainly focused on workers from fluorochemical or fluoropolymer manufacturing plants. To the best of our knowledge, there is no study focusing on the exposure to PFASs during the manufacturing of textiles.…”
Section: Environmental Science and Technologymentioning
confidence: 99%
“…Time trend studies show that PFOA levels are significantly associated with the time being exposed to PFOA, i.e. during work as a ski waxer [102][103][104]. And recent studies strongly indicate that PFOA levels increase with age [105,106].…”
Section: Assessment Of the Bioaccumulation Potentialmentioning
confidence: 99%